Role of nebulised magnesium sulfate in treating acute asthma in children: a systematic review and meta-analysis - Jogender Kumar; Prawin Kumar; Jagdish Prasad Goyal; Atul Gupta; Jitendra Meena; Kalyana Prabhakaran; Nikhil Rajvanshi (BMJ Publishing Group, 2024)
Objectives To review the efficacy of nebulised magnesium sulfate (MgSO4) in acute asthma in children.Methods The authors searched Medline, Embase, Web of Science and Cochrane Library for randomised controlled trials (RCTs) published until 15 December 2023. RCTs were included if they compared the efficacy and safety of nebulised MgSO4 as a second-line agent in children presenting with acute asthma exacerbation. A random-effects meta-analysis was performed, and the Risk of Bias V.2 tool was used to assess the biases among them.Results 10 RCTs enrolling 2301 children with acute asthma were included. All trials were placebo controlled and administered nebulised MgSO4/placebo and salbutamol (±ipratropium bromide). There was no significant difference in Composite Asthma Severity Score between the two groups (6 RCTs, 1953 participants; standardised mean difference: −0.09; 95% CI: −0.2 to +0.02, I2=21%). Children in the MgSO4 group have significantly better peak expiratory flow rate (% predicted) than the control group (2 RCTs, 145 participants; mean difference: 19.3; 95% CI: 8.9 to 29.8; I2=0%). There was no difference in the need for hospitalisation, intensive care unit admission or duration of hospital stay. Adverse events were minor, infrequent (7.3%) and similar among the two groups.Conclusions There is low-certainty evidence that nebulised MgSO4 as an add-on second-line therapy for acute asthma in children does not reduce asthma severity or a need for hospitalisation. However, it was associated with slightly better lung functions. The current evidence does not support the routine use of nebulised MgSO4 in paediatric acute asthma management.PROSPERO registration number CRD42022373692.